Methylglyoxal causes pain and hyperalgesia in human through C-fiber activation - Düll, Miriam; Riegel, Kathrin; Tappenbeck, Julia; Ries, Vivien; Strupf, Marion; Fleming, Thomas; Sauer, Susanne K.; Namer, Barbara (Pain, 2019)
The endogenous metabolite methylglyoxal (MG) accumulates in diabetic patients with neuropathic pain. Methylglyoxal could be a mediator of diabetes-induced neuropathic pain through TRPA1 activation and sensitization of the voltage-gated sodium channel subtype 1.8. In this study, we tested the algogenic and sensitizing effect of MG in healthy human subjects using intracutaneous microinjections. The involvement of C fibers was assessed through selective A-fiber nerve block, axon-reflex-erythema, and through single nerve fiber recordings in humans (microneurography). Involvement of the transduction channels TRPA1 and TRPV1 in MG-induced pain sensation was investigated with specific ion channel blockers. We showed for the first time in healthy humans that MG induces pain, axon-reflex-erythema, and long-lasting hyperalgesia through the activation of C nociceptors. Predominantly, the subclass of mechano-insensitive C fibers is activated by MG. A fibers contribute only negligibly to the burning pain sensation. Selective pharmacological blockade of TRPA1 or TRPV1 showed that TRPA1 is crucially involved in MG-induced chemical pain sensation and heat hyperalgesia. In conclusion, the actions of MG through TRPA1 activation on predominantly mechano-insensitive C fibers might be involved in spontaneously perceived pain in diabetic neuropathy and hyperalgesia as well as allodynia.